# Homework Help: Discretize using a forward-Euler scheme

Tags:
1. Jan 15, 2016

### Linder88

1. The problem statement, all variables and given/known data
Consider the differential equation

y'''-y''=u

Discretize (1) using a forward-Euler scheme with sampling period

\Delta=1

and find the transfer function between u(k) and y(k)
2. Relevant equations
The Euler method is
$$y_{n+1}=y_n+hf(x_n,y_n)$$

3. The attempt at a solution
Laplace transform of (1) yields
$$s^3Y(s)-s^2Y(s)=U(s)$$
From my teacher I know that
$$s=\frac{z-1}{\Delta}$$
Using this formula on the Laplace transform of (1) yields
$$\bigg(\frac{z-1}{\Delta}\bigg)^3y_{k}-\bigg(\frac{z-1}{\Delta}\bigg)^2{y_k}=u_k$$
Substituting (2) in this equation yields
$$(z-1)^3y_k-(z-1)^2y_k=u_k$$
$$y_{k+3}-y_{k+2}=u_k$$
Now I want to find the transfer function between u(k) and y(k) but I don't see and y(k).
Can somebody please help me? I have my exam tomorrow!

Last edited: Jan 15, 2016
2. Jan 15, 2016

### BvU

I can't follow the step
to $$y_{k+3}-y_{k+2}=u_k$$Could you explain why this doesn't work out to e.g. $${y_k \over u_k}\ = \ {1\over (z−1)^3 − (z−1)^2 } {\rm\quad ?}$$

Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted